Mercury anomalies within the lower Cambrian (stage 2–3) in South China: Links between volcanic events and paleoecology - Wang, Zhanghu; Tan, Jingqiang; Boyle, Richard; Wang, Wenhui; Kang, Xun; Dick, Jeffrey; Lyu, Qiao (Palaeogeography, palaeoclimatology, palaeoecology, 2020)
The early Cambrian period is characterized by not only the explosive radiation of metazoans, but also several mass extinction events. Mercury (Hg) enrichment is now widely used as a proxy for volcanic input, with implications for the CO2 and temperature to which the biosphere was subject during these events. Here, we report the oldest mercury anomaly records from organic matter in the Phanerozoic, taken from two wells (Xa1 and Xb1), which represent early Cambrian slope to basin sections in South China. The first mercury anomaly coincided with both a negative carbon isotope excursion (Shiyantou Carbon isotope Excursion, SHICE) recorded in Cambrian Stage 2, and the disappearance of small shelly fossil assemblages (SSFs). The above events may have been closely related to an unknown large igneous province (LIP) in Earth's history. Two subsequent mercury anomalies occur in conjunction with phases of hydrothermal (submarine volcanic) events. In addition, we find evidence for photic zone euxinia (PZE) in some parts of the depositional environment, with iron-speciation data suggestive of dissolved H2S concentrations close to 10 mM in the basin environment, along with hyper-enrichment of V and Zn in shale suggesting the presence of dissolved H2S in the photic zone. We interpret our results as providing potential evidence for links between volcanism, widespread euxinia, and early Cambrian faunal changes. •The oldest mercury anomaly since the Palaeozoic was determined.•Volcanic events with carbon isotope excursion coincide with biotic extinction.•Geochemical data reflected redox stratification of the water column.•Hyper-enrichments of V and Zn in black shales indicated extreme euxinic conditions.•Photic zone euxinia event occurred in South China in the early Cambrian.